Error Analysis in Arabic Language among Engineering Student at Universiti Malaysia Pahang - Mohammad Baihaqi, Hasni; Mardhiyyah, Zamani; Shahrel Ahmad, Shuhel Ahmad (2017)
This study aims to analyze the errors in Arabic Language among students who learn Arabic for Beginners course (UHF 1141) at the Universiti Malaysia Pahang. The study was carried out against the 30 students, who took Arabic for Beginners course, using their written test paper as data of the study. This analysis is adapted using the theory of Corder (1967). According to Corder (1981), the error or offense language is a form of the use of language that deviated from the language system received by the native speakers and the errors cover language aspect, such as grammar, spelling, pronunciation, word usage, term, etc. Study data is amplified with the questionnaire data carried out against 4 teachers and 30 students who attended the course. The findings show that students made the error in grammar, such as error in aspect, phrases, sentences and orthography of the word. The study also found that the orthography error, which is the spelling error is mostly committed by the students (54 errors). The second highest error is the error in word aspect, i.e. feminine and masculine (45 errors), followed by word aspect of Singular, duo and Plural (36 errors). The error in pronouns followed by (21 errors). The lowest error in terms of frequency is the error in the use of number aspect (15 errors). Based on the questionnaire, most students made grammar mistakes due to disruption of native language, the attitude of students and the language environment in university. To address this problem, language teaching and learning strategies should be increased. Continuous guidance from the teacher/lecturer, language learning through multimedia and organizing activities such as quizzes, acting and visit are essentials in encouraging Arabic language learning among foreign students.